Size, species and audience type influence heterospecific female–female competition. (January 2020) - Makowicz, A.M.; Murray, L.; Schlupp, I.
Abstract : Female–female competition for mates can be as intense as male–male competition, but it has received little attention until recently. Typically, such competition is expressed as context-dependent aggressive encounters between individuals of the same species within a complex social environment. Unlike male competition, in cases of sexual parasitism, female competition includes important heterospecific interactions. We explore how competitor body size and species influence female–female aggression in a sexual–unisexual mating system where heterospecific females compete for males of the sexual species. Specifically, we examined whether (1) the size and species of female competitors and (2) the sex and species of an audience influence female–female aggression in sailfin mollies, Poecilia latipinna . We found that competitor body size had a secondary effect on the amount of aggression a female performed when compared to the species of her female competitor. Female sailfin mollies were more aggressive towards conspecifics than they were towards Amazon mollies, Poecilia formosa, especially in front of a sailfin molly male and female audience. These results demonstrate that the social environment greatly influences how females regulate their aggressive behaviours, and they highlight not only the role of female competition for males, but also the importance of understanding the impact of the social environment on female competition. Highlights: We examined female–female aggression in a sexual–unisexual molly mating system. Body size was not as important as species in determining aggressiveness. Body size influenced tail beats; species influenced the number of bites. Total aggression depended on body size, species and sex of the conspecific audience. Sexual sailfin mollies received more aggression from unisexual Amazon mollies.